Cost-benefit assessment of manufacturing system using comprehensive value flow analysis. (15th March 2022) - Sun, Jingchao; Na, Hongming; Yan, Tianyi; Che, Zichang; Qiu, Ziyang; Yuan, Yuxing; Li, Yingnan; Du, Tao; Song, Yanli; Fang, Xin
Highlights: A novel assessment method is proposed to increase benefits of manufacturing systems. Networks of material, energy, environment and economic are thoroughly considered. The comprehensive value flow is presented considering the exergy of energy. Feasible suggestions are therefore proposed to improve the performance in energy and economic. It is confirmed efficient in following case study with dramatic improved comprehensive benefits. Abstract: The comprehensive assessment of the performance of production system is a crucial activity for the implementation of sustainable production practices for the manufacturing industry. The existing relevant assessment methods are not comprehensive enough, especially in terms of material, energy, environment and economics. They lack specific economic performance indicators based on industrial systematic analysis, and couldn't give a clear explanation for the comprehensive value flow in the production process. This paper proposes a novel assessment method, called Comprehensive Value Flow Analysis, which aims to describe and classify activities in the network of material, energy, environment and economics according to systematic energy saving and lean production theory. The drawing method of comprehensive value flow and a new cost-benefit indicator named advanced cost-profit ratio are proposed for identifying quantitatively the criticalities related to activities, processes, systems, technologies, etc. And significant suggestions for the improvement strategies implementation are given. A case study of a typical iron and steel enterprise has been evaluated using this method. Moreover, it successfully identifies the issues about energy structure, production structure and technologies application with a global perspective by explicating the comprehensive value flow and analyzing the relevant indicators, and then offering some valuable suggestions for sustainable development. The analysis highlighted that every enterprise has its own marginal benefits according to the production status and market economy. In summary, it is favorable to make real and effective decisions on improvement for the comprehensive benefits of enterprises.